Effect of geometrical modifications on the mixing and enzymatic conversion of structured lipids in internal-loop airlift bioreactors - de Oliveira, Daniele Gonçalves [UNESP]; Mazziero, Vítor Teixeira [UNESP]; Picão, Bruno Willian [UNESP]; Ribeiro, Renata Maria de Magalhães Gomes Pontes; Esperança, Mateus Nordi; de Paula, Ariela Veloso [UNESP]; Cerri, Marcel Otavio [UNESP] (Elsevier, 2024)
Airlift bioreactors present a compelling alternative for reactions utilizing immobilized enzymes, offering advantages over stirred tank and packed-bed reactors. This study proposed a new configuration for an internal-loop airlift bioreactor (1 L working volume) to produce structured triglycerides using immobilized lipases in a viscous fluid. Different internal tube configurations were studied, which varied in diameter (17.5–78.6 mm), angle (-2,0,5,10 and 12°), and the addition of a rounded bottom to the bioreactor, which improved the three-phase mixture flow. The hydrodynamic effect caused by these modifications was evaluated by studying the mixing time. The best internal tube configuration, featuring a truncated cone-shaped, exhibited a 5° angle and a 64.5-mm diameter, resulting in a mixing time of 54 s. This value was about three times less than the mixing time obtained by the standard tube (171 s) at 2 vvm. Sequentially, grape seed oil acidolysis reactions with capric acid (C10) catalyzed by the Lipozyme RM IM were performed, obtaining structured MLM triglycerides with an incorporation degree of 32.32% ± 1.01%. These results indicated good biocatalyst operational stability, with a half-life of 14.13 days. Thus, this work unveils a new configuration for an airlift bioreactor collectively driving promising advancements in structured lipid production.
Keywords: Airlift bioreactor; Dietary triglycerides; Geometric modifications; Immobilized lipase; Mixing time; Multiphase mixing